2018
DOI: 10.3390/biom8040162
|View full text |Cite
|
Sign up to set email alerts
|

pH-Induced Folding of the Caspase-Cleaved Par-4 Tumor Suppressor: Evidence of Structure Outside of the Coiled Coil Domain

Abstract: Prostate apoptosis response-4 (Par-4) is a 38 kDa largely intrinsically disordered tumor suppressor protein that functions in cancer cell apoptosis. Par-4 down-regulation is often observed in cancer while up-regulation is characteristic of neurodegenerative conditions such as Alzheimer’s disease. Cleavage of Par-4 by caspase-3 activates tumor suppression via formation of an approximately 25 kDa fragment (cl-Par-4) that enters the nucleus and inhibits Bcl-2 and NF-ƙB, which function in pro-survival pathways. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 94 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…This region of the protein can be further subdivided as follows: ( Figure 1 a): the SAC (Selective for Apoptosis induction in Cancer cells) domain, the CC (Coiled-Coil) domain, and the Linker between these two domains. In addition, the SAC domain contains an NLS (Nuclear Localization Signal) near its N-terminus, and the CC domain contains an LZ (Leucine Zipper) domain which comprises its C-terminal half [ 23 ]. Prediction of disorder in these domains was done by using DISOPRED3, which utilizes X-ray diffraction databases ( Figure 1 b) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This region of the protein can be further subdivided as follows: ( Figure 1 a): the SAC (Selective for Apoptosis induction in Cancer cells) domain, the CC (Coiled-Coil) domain, and the Linker between these two domains. In addition, the SAC domain contains an NLS (Nuclear Localization Signal) near its N-terminus, and the CC domain contains an LZ (Leucine Zipper) domain which comprises its C-terminal half [ 23 ]. Prediction of disorder in these domains was done by using DISOPRED3, which utilizes X-ray diffraction databases ( Figure 1 b) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering a probability of 0.5 (dashed line) as the demarcation line, the analysis clearly predicts order in the CC domain and disorder in the Linker, while the SAC domain has intermediate character, approaching the order/disorder line. Previous sequence analysis also showed mixed order/disorder propensity and some helical character in the SAC domain, and so order in the SAC domain would not be surprising, under the right conditions [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression and purification was performed according to published procedures . Briefly, cl‐Par‐4 in the H‐MBP‐3C expression vector was expressed in BL21(DE3) CodonPlus Escherichia coli grown in LB with 100 μg·mL −1 ampicillin at 37 °C, and purified using a His‐Trap HP column (GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies have shown that cl‐Par‐4 is predominantly disordered under typical physiological conditions, but that acidic pH promotes increased helical content . Disordered proteins often fold under extreme conditions due to various stabilizing factors .…”
Section: Introductionmentioning
confidence: 99%